Freight demand modeling : tools for public-sector decision making : summary of a conference - Hancock, Kathleen L. (Transportation Research Board, 2008)
On September 2527, 2006, the Transportation Research Board (TRB) convened the conference on Freight Demand Modeling: Tools for Public-Sector Decision Making in Washington, D.C. The conference sponsored jointly by TRB, the Federal Highway Administration, the U.S. Army Corps of Engineers, the Research and Innovative Technology Administration, and the Federal Railroad Administration brought together approximately 120 individuals from across the freight transportation communities, at national, state, regional, and local levels and from the public and private sectors and academia. The conference benefited from the contributions of international speakers and participants from Canada, the Netherlands, Sweden, Finland, Australia, and Chile. The conference was designed to complement the Federal Highway Administration's work on the Freight Model Improvement Program and focused on modeling methodologies, applications of existing models at the national and local levels (including international examples), and related data needed to support modeling efforts. The objectives were to engage members of the freight transportation community in examining current modeling practice and identifying areas where improvement may be needed.
"September 25-27, 2006, Keck Center of the National Academies, Washington, D.C."
Sponsored by Transportation Research Board and others.
Keywords: Freight and freightage -- Estimates -- Congresses.; Freight and freightage -- Congresses.; elektronické knihy; electronic books